Comparing paper-based and mobile application for rank-based peer assessment in interprofessional education: before, during, and after the COVID-19 pandemic - Doni Widyandana; Prattama Santoso Utomo; Ide Pustaka Setiawan; Yustina Tyas Kurniawati; Sucheta Dandekar (BMC Medical Education)
Abstract Background Education was affected during the COVID-19 pandemic, and there was a need to adapt the learning approaches to the situation. At the University of Gadjah Mada, many essential soft skills of healthcare professionals are taught using the interprofessional education (IPE) approach on-site. Our university responded to this crisis by offering online classes and similar types of training. Post-administration of the course, a peer-assessment was conducted, and it was used to provide feedback on the work or performance of peers among students. Peer assessment was done using paper-based and a mobile application during COVID-19. This study aimed to share a best practice for the implementation of a rank-based peer-assessment application for longitudinal interprofessional education in the community setting and to compare the score distribution of a rank-based peer-assessment before and after using mobile application. Methods Quantitative research design was used by processing secondary data on student peer assessment scores from 3 bachelor programs (medicine, nursing, nutritionist) Community and Family Health Care with Interprofessional Education (CFHC-IPE) in Faculty of Medicine, Nursing, and Public Health, Universitas Gadjah Mada. 4,790 students from 2018 to 2022 (5 years) were tracked before, during, and after the COVID-19 pandemic. The assessments carried out were offline, online, and blended learning, respectively. The assessment was carried out using a paper-based method before and during the pandemic, online-based with a mobile application was used. Thus, the peer-assessment was conducted manually or using paper-based method using a 5-rank scoring system. In 2019, the peer assessment was carried out using a mobile application and applied a 10-rank scoring system. Results The rank-based peer assessment can be well implemented to make students assess their friends more objectively, with an average score 82.02 ± 8.68. The rightward shift in the distribution of scores indicates that the average score has improved after using the mobile application compared to before its use. (82.02 ± 8.68 vs. 62.39 ± 11.13, p < 0.05). Conclusion The implementation of rank-based peer-assessment using a mobile application was well received during and after the pandemic by interprofessional undergraduate students. The online system made the assessment more objective and the average grades were seen to be better.